Authenticity vs. Inauthenticity in Oscar Wilde’s The Importance of Being Earnest - Khalil, Md. Ibrahim (International Journal of Language and Literary Studies, 2021)
Unlike other living creatures, human being requires an authentic life to reflect the true self and independence. Due to the limitations and complicacies of life, either personal or from the surroundings, people sometimes play inauthentic roles and express inconsistent statements. Wilde’s play ‘The Importance of Being Earnest’ represents the same situation where two protagonists Jack Worthing and Algernon Moncireff frequently change their valid identity and address for abundant freedom and worldly pleasure. Considering two fundamental existentialistic concerns such as authenticity and inauthenticity along with qualitative and descriptive analysis method, the study evaluates how authentic or inauthentic decisions Algernon and Jack have made to transform their long carried name, definite identity and diversified location. It highlights how Wilde’s major characters are intertwined with complicated relationships affecting self-motivated decision, choice and freedom. Nevertheless, the study takes into account all the self-contradictory commitments of both Algernon and Jack Worthing and their ridiculous attitude towards religious perception. Finally, it inspects the authenticity of the name “Earnest” for what both Cecily Cardew and Gwendolen Fairfax always feel an inexorable urge and fervor.